All Questions Topic List
None Questions
Previous in All Question Next in All Question
Previous in None Next in None
Question Number 110288 by mathdave last updated on 28/Aug/20
Answered by bemath last updated on 28/Aug/20
Δbemath▽lety=vx⇒dy=vdx+xdv⇔(4vx−2x)dx=(x+vx)(vdx+xdv)(4v−2)dx=(1+v)(vdx+xdv)(4v−2)dx=(v+v2)dx+(x+vx)dv(3v−2−v2)dx=x(1+v)dv⇔−dxx=(1+v)dvv2−3v+2⇔−lnx+c=∫(1+v)dv(v−1)(v−2)⇔−lnx+c=3ln(v−2)−2ln(v−1)ln(Cx)=ln((v−2)3(v−1)2)⇔C(v−1)2=x(v−2)3C(y−xx)2=x(y−2xx)3C(y−x)2=(y−2x)3y(1)=3⇔C(3−1)2=(3−2)34C=1→C=14∴(y−x)2=4(y−2x)3
Commented by mathdave last updated on 28/Aug/20
goodwork
Terms of Service
Privacy Policy
Contact: info@tinkutara.com